PENGARUH PEMBERIAN RUMPUT RAJA (Pennisetum purpupoides) DAN TEBON JAGUNG TERHADAP KECERNAAN NDF DAN ADF PADA SAPI PO PEDET JANTAN - Siswanto, Dwi; Tulung, Bernat; Maaruf, Kartini; Waani, M. R.; Tindangen, M. M. (Universitas Sam Ratulangi, 2016)
THE EFFECTS OF OFFERING KING GRASS (Pennisetum purpupoides) AND CORN STOVER ON NDF AND ADF DIGESTIBILITY OF MALE ONGOLE CROSS BREED STEER CALVES. A research evaluating the effects of offering king grass (Pennisetum purpupoides) and corn stover as feed ingredients on NDF and ADF digestibility of male ongole cross breed steer calves. This study used five male ongole calf weighing Â± 100 kg. Latin Square design consisting of 5 treatments was used. The treatments were the ratio between the king grass and corn stover; R1 = 100% king grass, R2 = 75% king grass + 25% corn stover, R3 = 50% king grass + 50% corn stover, R4 = 25% king grass + 75% corn stover and R5 = 100% corn stover. The variables measured were digestibility of NDF and ADF. The results of analysis of variance showed that there were highly significant effects (P 0.05), while there were no significant different between R4 and R5 (P>0.05). Tukey test on ADF digestibility showed that there were no significant different among R1 (49.2%), R2 (58.03%), R3 (56.09%), and R4 (59.79%) (P >0.05), however R1 was significantly lower than R5 (65.32%) (P>0.05). There were no significant difference among R2 to R3, R4 and R5 (P>0.05). It can be concluded that biological value (NDF and ADF digestibility) of corn stover is higher compared to king grass. keywords: digestibility, king grass and corn stove